EVALUATING STABILITY OF RIVERBANKS REINFORCED WITH ROCKFILL COLUMNS - W. F. Abdulrazaq; M. C. Alfaro; J. A. Blatz (International Association of Lowland Technology, 2010)
This paper presents the results of stability analysis of natural and stabilized riverbanks. Limit Equilibrium Method (LEM) and Finite Element Method (FEM) were used in the analysis. In the FEM, two approaches were employed: 1) combined LEM and FEM, and 2) FEM with the shear strength reduction (SSR) technique. The limit equilibrium method and the finite element method of stability analysis produced similar calculated factor of safety values. This provides confidence that either method estimates similar factor of safety values for natural and stabilized riverbanks. Based on the FEM analysis, it was shown that the centre-to-centre spacing between columns plays a major role in increasing the factor of safety. The calculated maximum shear strain in the stabilized riverbanks is reduced with a closer spacing rows. This is important since lesser slope displacements are required to mobilize the necessary shear resistance for closer rockfill column spacing.